Farmers Bank of Virginia (Alexandria, Va.) records - Farmers Bank of Virginia (Alexandria, Va.)
Chiefly routine bank correspondence (1861-1862) to cashier William H. Marbury; also includes an earlier (circa 1830) memorial to the directors of the bank.
Collection material in English.
Keywords: Marbury, William H. -- Correspondence; Banks and banking -- Virginia -- Alexandria